The effect of foreign ownership on financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) - Agus Arman (Universitas Hayam Wuruk Perbanas, 2015)
The Regulation of Bank Indonesia (PBI) 2000 which states that foreign investors are allowed to take control of ownership up to 99% of domestic banks in Indonesia has been in a long debate, especially by academics. Some studies prove that the existence of foreign ownership brings benefit, but on other hand, it does not bring any benefit. The purpose of this study is to provide evidence related to the effect of foreign own-ership on financial performance of banking companies listed on IDX measured by Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return on Equity (ROE), and Non-Performing Loans (NPLs). The testing involved the samples of 14 banking issuers whose ownership was dominated by foreign investors. The data, 2 years before and after the presence of foreign ownership, were used to get the results related to the effect of foreign ownership on financial performance of banking companies in Indonesia. The results of this study show that there is a significant in-crease in LDR, there is an insignificant increase in CAR, there is an insignificant decrease in ROE, and there is a significant decrease in NPLs after the presence of foreign ownership on the banking companies listed on the Indonesia Stock Exchange.